Advances in atomic, molecular, and optical physics. - Berman, Paul R., 1945-; Arimondo, E.; Lin, Chun C. (Advances in atomic and molecular physics, 2011)
Advances in Atomic, Molecular, and Optical Physics publishes reviews of recent developments in a field which is in a state of rapid growth, as new experimental and theoretical techniques are used on many old and new problems. Topics covered include related applied areas, such as atmospheric science, astrophysics, surface physics and laser physics. Articles are written by distinguished experts, and contain both relevant review material and detailed descriptions of important recent developments.